From hermeneutics to exegesis : the trajectory of biblical interpretation - Malcolm, Matthew R., 1975- (B & H Academic, 2018)
"Interpreting the Bible requires theoretical discernment and practical know-how. A book that focuses solely on interpretive methods or deals exclusively with the philosophical underpinnings of interpretation fails to provide a full picture of how to read and study Scripture. Beginning with hermeneutics, Matthew Malcolm surveys the history of the discipline, engages with important theological issues, and arrives at a memorable depiction of what happens when fruitful interpretation takes place. After covering these foundational elements, Malcom focuses on exegesis. He helps readers understand the issues at stake in interpreting biblical passages, and provides a straightforward guide to writing an exegesis paper. Academically solid without being overwhelmingly detailed, this is a reliable guide to the important path from hermeneutics to exegesis."--